2005
DOI: 10.1097/01.wnf.0000166393.33781.87
|View full text |Cite
|
Sign up to set email alerts
|

Entacapone Increases Levodopa Exposure and Reduces Plasma Levodopa Variability When Used With Sinemet CR

Abstract: Entacapone is a catechol-O-methyltransferase (COMT) inhibitor used as an adjunct to levodopa/dopa decarboxylase inhibitors in the treatment of Parkinson's disease. Entacapone increases the bioavailability and reduces the daily variation of plasma levodopa when administered with standard levodopa preparations. These parameters were studied when entacapone was administered with a controlled-release levodopa preparation after repeated administrations throughout the day in 16 healthy male volunteers. On 2 test day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 29 publications
1
8
1
Order By: Relevance
“…This agrees with earlier studies conducted in healthy subjects [2] and patients with PD [5], which have shown that a single administration of LC and entacapone does not increase the C max of levodopa. With different dosing regimens, similar kinds of results (regarding t 1/2 , C min , C max , and AUC of levodopa) have been reported with repeated dosing of entacapone administered together with standard release levodopa/carbidopa [4][5] or with controlled-release levodopa/carbidopa [18]. It has also been reported that co-administration of tolcapone t.i.d.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…This agrees with earlier studies conducted in healthy subjects [2] and patients with PD [5], which have shown that a single administration of LC and entacapone does not increase the C max of levodopa. With different dosing regimens, similar kinds of results (regarding t 1/2 , C min , C max , and AUC of levodopa) have been reported with repeated dosing of entacapone administered together with standard release levodopa/carbidopa [4][5] or with controlled-release levodopa/carbidopa [18]. It has also been reported that co-administration of tolcapone t.i.d.…”
Section: Discussionsupporting
confidence: 52%
“…The sample-size calculation was based on a previous study with four daily doses of controlled-release LC 100/25 mg and entacapone 200 mg given at 4-h intervals [18]. The sample size needed to produce a statistical power of 80% in this study was nine subjects (with a significance level of 5%).…”
Section: Discussionmentioning
confidence: 99%
“…Single doses do not cause a rise in either the maximal plasma concentration (C max ) or the time to reach maximal plasma concentration (T max ), 393,394 but chronic dosing is associated with accumulation over the course of the day. COMT inhibitors are effective when administered in conjunction with either regular or sustained-release Sinemet 395 and increase interdose, trough, and mean levodopa concentrations. 396 Thus, administration of levodopa plus a COMT inhibitor results in smoother plasma levodopa levels and more continuous brain availability compared with levodopa alone.…”
Section: Time (Months)mentioning
confidence: 99%
“…Parkinson's disease (PD) is a chronic, progressive neurodegenerative disease with neuropathological hallmarks of the loss of dopaminergic neurons in the Sub-DOI: 10.1159/000479555 stantia Nigra pars compact and the reduction of dopamine in striatum. The clinical features of PD are akinesia, bradykinesia, rigidity and tremors, which are known to be directly related to dopaminergic striatal loss [1].…”
Section: Introductionmentioning
confidence: 99%